2005
DOI: 10.1097/00000542-200509000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Postpolio Syndrome and Anesthesia

Abstract: The development of polio vaccines 50 yr ago essentially halted childhood polio epidemics in the industrialized world. During the past quarter century, a constellation of delayed neuromuscular symptoms, called postpolio syndrome, became recognized among the aging polio survivors. The prevalence of postpolio syndrome in the U.S. population is estimated to be in the hundreds of thousands. The most common symptoms are fatigue, pain, and new onset weakness thought to be related to delayed deterioration of motor neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 37 publications
0
50
0
9
Order By: Relevance
“…In addition to that, 40% of PPS patients have some degree of respiratory dysfunction. [1] Emergence from anaesthesia is thus, the period where utmost caution has to be exerted. Two of the case reports [5,7] available and mentioned earlier have reported unanticipated postoperative respiratory failure, one of them reporting a cardiopulmonary arrest one hour postoperatively where the patient could not be revived.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, 40% of PPS patients have some degree of respiratory dysfunction. [1] Emergence from anaesthesia is thus, the period where utmost caution has to be exerted. Two of the case reports [5,7] available and mentioned earlier have reported unanticipated postoperative respiratory failure, one of them reporting a cardiopulmonary arrest one hour postoperatively where the patient could not be revived.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Along with limb paralysis, these patients also frequently present with spinal curvature deformities of varied degrees at different levels of the spine. [1] A study carried out in 2003, [2] reported poliomyelitis infection survivors, to have a high incidence of dyslipidemia and a high prevalence of two or more coronary artery disease risk factors. With advancing age, this population, of the past century, now frequently presents to us for elective cardiac or emergency cardiac surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptoms are fatigue, pain, and new onset weakness thought to be related to a delayed deterioration of the motor neuron function. 8,9 Female survivors of polio have an elevated risk for pregnancy complications, operative delivery, and adverse perinatal outcomes. 10,11 Veiby et al 10 noted that pre-eclampsia was significantly more frequent in patients with poliomyelitis, irrespective of maternal age or parity.…”
Section: Discussionmentioning
confidence: 99%
“…This situation has been described as the postpolio syndrome [1,2]. Patients having this disorder have excessive susceptibility to neuromuscular blockers [2,3]. We report the case of a patient who had no evidence of postpolio syndrome, but nevertheless showed excessive sensitivity to nondepolarizing muscle relaxants, and developed weakness while in the intensive care unit (ICU).…”
Section: Introductionmentioning
confidence: 94%
“…Such polio survivors can develop new onset of progressive muscle weakness and fatigue in skeletal or bulbar muscles more than 15 years later. This situation has been described as the postpolio syndrome [1,2]. Patients having this disorder have excessive susceptibility to neuromuscular blockers [2,3].…”
Section: Introductionmentioning
confidence: 99%